Resolving the Inconsistency Between National and EU Motor Insurance Law. Was Factortame the Solution Nobody Sought?. Issue 1 (January 2021) - Marson, James; Alissa, Hasan; Ferris, Katy
Abstract: In this Article, we argue that the uncertainty of UK national motor vehicle insurance law—when viewed with respect to its European Union (EU) parent, the Motor Vehicle Insurance Directive (MVID)—was never satisfactorily addressed, primarily when using the remedy available through the non-contractual liability of the State. The EU enforcement mechanisms were equally haphazard in their effectiveness and success in affording rights to third-party victims. Given the link between the MVID and the free movement of persons and goods, on which the harmonization of insurance protection was based, we present the first Article establishing an argument that those offending aspects of UK national law should have been disapplied. The UK has concluded its agreement to withdraw its membership of the EU—and thus no longer to be bound by EU law and the jurisprudence of the Court of Justice. Yet until the transitional period ends, the UK remained aligned to EU law and those defects present in national law should have been remedied. Therefore, the remedy issued from the Factortame line of case authorities may have proven to be the most effective way to grant access to rights which were denied to third-party victims in the UK. Here we present a justification for its application.